Development of school-based language bridging training program for grade IV teachers - De Castro, Xerxes M.
The government of the Philippines recognized the value of using the mother tongue (MT) as a medium of instruction (MOI) as well as learning literacy in the early grades by including a provision for Mother Tongue-Based Multilingual Education (MTB-MLE) in its K to 12 Basic Education Curriculum. The Department of Education (DepEd) has also released several issuances that support the use of MT in delivering lessons to learners. DepEd has organized several trainings on MTB-MLE since 2012 to address the need of teachers to be updated with trends in teaching and classroom management. However, attention was primarily given to Kindergarten to Grade 3 (K to 3) teachers. This could be attributed to the idea that the Philippine MTB-MLE program follows the early-exit design, which means that learners receive instruction exclusively in the MT only until Grade 3. Although Republic Act No. 10533 of 2013 requires a gradual transition to using Filipino and English from Grades 4 to 6, the transition that occurs between Grade 3 and Grade 4 does not follow the ideal bridging plan by UNESCO. This study sought to address this issue in one school by training its Grade 4 teachers on bridging among languages as they transition between L1 and L2 instruction. The specific research questions are: (1) What school-based training on bridging practices can be designed based on Grade 4 teachers’ pre-identified challenges? and (2) How do Grade 4 teachers respond to school-based training on bridging practices? The study is descriptive-qualitative research that focused on the development of a school-based training program that highlights bridging, an important instructional strategy that connects the different languages of instruction. The developed training program is called Pagtutulay: Bridging Languages in Philippine MTB-MLE for Grade 4 Teachers. Teachers’ responses to the training were also explored to assess the possibility for sustainability and replicability. A group of Grade 4 teachers (whose students’ MT is Kapampangan) from one public school in Central Luzon participated in the training program. A Bridging Mentor who was also a teacher in the same school delivered the eight sessions using a researcher-designed module. Instruments to gather needs analysis and evaluation data included a questionnaire, FGD schedule, classroom observation form, and evaluation tools. Analysis was done with the use of SPSS and NVivo. The first research question on training program development was answered by assessing the needs of participants to inform the design and content of the program. The identified needs include: (1) teachers’ lack of training on MTB-MLE, (2) teachers’ potential opportunities to apply bridging in Grade 4 lessons, (3) translation as a bridging strategy, (4) teachers’ non-use of MT as a permitted auxiliary LOI in Grade 4, (5) teachers’ identified challenges, and (6) teachers’ willingness to learn new strategies. The steps conducted to develop the training program were: (1) review of MTB-MLE, transfer, bridging, and training principles, (2) data generation, (3) analysis of needs data, (4) development of program design, and (5) development of program materials. The participating teachers’ responses were analyzed to answer the second research question. The teachers had the willingness to be trained, and they reported that the school-based training was effective because of its relevance to their practice. They were able to identify factors that are necessary to implement the bridging strategies. They were also able to apply some of the newly-learned strategies to their classes, and they committed to continue applying them in class. Moreover, the teachers recognized the value of bridging at their level when they saw a positive change in pupil behavior. However, it appeared that the teachers need further training to fully develop their skills in the different bridging strategies.